The Power Quality Analysis of Electrical Installation at Commercial Center - Mayen, Akuak ayor akuak; Syamsiana, Ika Noer; Nofvowan, Anang Dasa (Elposys: Jurnal Sistem Kelistrikan, 2024)
For many years, power quality analysis has constantly been carried out at the power stations or sub-stations using the data collected at the data Centre of the power plant. However, this practice has proven to be erroneous and tedious to determine the exactly power quality problem especially when it comes to commercial facilities. Therefore, a revised approach of analysis for the power quality problems at the sites where they occur has been used in this research. This is because of the sensitivity of modern electronic equipment used in commercial facilities and also the need for accuracy of the data measurements carried out at the sites henceforth, with accurate data measurement, we can easily identify the power quality issues. Through-out this research, load unbalance of 28% was found. The solution to load unbalance was to balance the loads to 3,3% among the three phases and power losses caused by this unbalance current were calculated. Although the neutral conductor remained unchanged, harmonics especially triplen-harmonics was found to be more 10% recommended by IEC standards, therefore active harmonic filter of 200A was installed at the main panel board to reduce the losses caused by harmonics at the facility.